A Randomized Comparison Between Ultrasound- and Fluoroscopy-Guided Sacral Lateral Branch Blocks. Issue 3 (May 2017) - Finlayson, Roderick J.; Etheridge, John-Paul B.; Elgueta, Maria Francisca; Thonnagith, Atikun; De Villiers, Frederick; Nelems, Bill; Tran, De Q.
Abstract : Background and Objectives: This randomized trial compared ultrasound (US)- and fluoroscopy-guided sacral lateral branch (SLB) blocks. We hypothesized that US would require a shorter performance time. Methods: Forty patients who required unilateral sacral lateral branch blocks for chronic low back pain were randomized to US or fluoroscopy guidance. Before the performance of the assigned block, an investigator who was not involved in patient care carried out baseline analgesic testing. With US, the dorsal sacroiliac ligament, the sacroiliac joint, and the interosseous ligament were probed with a 22-gauge block needle. The patient was asked to rate the level of discomfort using an 11-point numerical rating scale. After the analgesic test, attending anesthesiologists or supervised trainees carried out the SLB blocks. The local anesthetic agent (lidocaine 2%) was identical in all subjects. In the US group, local anesthetic (1.5 mL) was first injected on the lateral crest at the mid-point between S2 and S3. Subsequently, 2 more injections of 0.5 mL were carried out on the lateral crest, immediately cephalad to S2 and at the S1 level. In the fluoroscopy group, SLB blocks were performed according to a previously described 17-injection technique, which involves 9 skin entry sites and the targeting of the L5 posterior root and S1-S3 sacral lateral branches. A 0.4-mL volume of local anesthetic was deposited at each target point. The performance time, number of needle passes, and the incidence of vascular breach were recorded during the performance of the block. Twenty minutes after the end of local anesthetic injection, the same investigator who performed preblock analgesic testing carried out postblock testing in an identical manner. Results: Compared with fluoroscopy, the US technique was associated with a shorter performance time (267.5 ± 99.3 vs 628.7 ± 120.3 seconds; P < 0.001), fewer needle passes and a lower incidence of vascular breach (0 vs 10 occurrences; P = 0.001). However, the block effect (ie, the proportional decrease in numerical rating scale between preblock and postblock analgesic testing) was similar in both groups. Furthermore, no statistical differences were found in the proportions of patients achieving complete analgesia at each test site. The level of experience (ie, expert vs novice operator) significantly affected performance time with US but not with fluoroscopy. No procedural complications were recorded with either imaging modality during the 30-day follow-up period. Conclusions: Compared with their fluoroscopic counterparts, US-guided SLB blocks require a shorter performance time as well as fewer needle passes and carry a lower risk of vascular breach.